Pendampingan Percepatan Penurunan Stunting Melalui Pengolahan Kelimpahan Lele Dan Daun Kelor Di Kecamatan Kedungbanteng Banyumas - Hanum, Fauziah; Hikmanti, Ariyana; Sutiningsih (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
ABSTRACT Catfish is one of the livestock fish commodities that has great potential to be developed, because it has a high omega content that is beneficial for the human body, especially children who are experiencing physical development. The abundance of catfish and moringa leaves in Dawuhan Kulon Village, Kedungbanteng District, which are local foods, can be utilized to become processed foods that have added value in terms of nutrition that will affect their growth and development. Therefore, it is necessary to make efforts to improve community skills in processing local foods (catfish and moringa leaves) which are made into nuggets and making product packaging that is safe for processed foods for toddlers. The implementation method consists of the preparation stage, implementation of monitoring and evaluation. At the preparation stage, it is in the form of preparation of tools, human resources and a place of manufacture. The process of making and monitoring evaluation. Counseling was provided to 47 participants, mothers and cadres about stunting and pre-test and post-test evaluations were carried out. The average knowledge of cadres and mothers of toddlers increased after counseling, and the majority of toddlers aged 2-3 years were 18 (48.65%), while the gender of the toddlers was mostly female (56.76%), the nutritional status of very short children was 9 children (24.32%), and short children (75.68%). Keywords : Stunting, catfish and moringa leaves, nuggets